Enforcement of The Law against Children Performing The Crime of Baby Availment (Klaten Police Case Study) - Sekar Nur Hidayati; Marisa Kurnianingsih (Universitas Muhammadiyah Surakarta, 2023)
This research aims to examine law enforcement against children who are perpetrators of the criminal act of baby dumping committed by the Klaten Resort Police. The act of baby dumping is an act carried out by someone who deliberately leaves a newborn child to be found by someone else with the intention of letting the child escape. his responsibility. In Diklaten there has been a case of baby dumping carried out by class III junior high school students. This research uses empirical juridical methods of a qualitative type with interviews conducted at the Klaten Police Station. Regarding criminal law, children as perpetrators of baby dumping are regulated in criminal law regulations in the Criminal Code and criminal law regulations outside the Criminal Code. Protection of children's rights as perpetrators of baby dumping in the criminal justice process can be carried out through diversion efforts such as those carried out in the case of baby dumping in Wurung Rejo Hamlet, Bawukan Village, Kemalang sub-district, Kab. The obstacles faced by the police in enforcing the law against children who commit the crime of dumping babies are divided into two: preventive, namely that the community has narrow thinking and does not want to develop, even though there has been education about the dangers of free sex and its impacts as well as other legal education, while repressive, namely that the police find it difficult to find perpetrators because people who are pregnant outside of marriage hide their pregnancy from family, society and peers.